DETECTION OF ANTIBODY TO NEWCASTLE DISEASE VIRUS IN HUMAN SERA IN PAKISTAN - A. Ahad; M. Rabbani; T. Yaqub; A. Mahmood; Z. H. Kuthu; M. Z. Shabbir; A. A. Sheikh; H. Gohar (Journal of Animal and Plant Sciences, 2013)
Ability of Newcastle disease virus (NDV) to elicit antibody response and clinical illness was assessed in poultry workers from 12 districts of Punjab, Khyber Pakhtoonkhwa and capital areas of Pakistan through a cross sectional sero- surveillance. Blood samples collected from 465 exposed and 25 unexposed individuals were tested for antibody titer against NDV through modified horse RBC haemagglutination inhibition (HI) test. Among different worker groups, the highest geometric mean titer (GMT) value of 149 was recorded for vaccinator’s group followed by poultry attendants (86); lab technicians (65); veterinarians (61) and butchers (26). Among in different districts, the highest GMT value (160) was recorded for Haripur, Sialkot and Toba Tek Singh districts followed by Multan (139); Gujranwala (130); Faisalabad (113); Bahawalnagar (98); Lahore (80); Rawalpindi (75); Chakwal (53); Sheikhupura (53) and Islamabad (26). Occupation/group and district wise the highest seropositivity was recorded for vaccinator’s group (85.71%) and for Toba Tek Singh district (82.14%) whereas that of the lowest was recorded for butcher’s group (20.63%) and for Islamabad district (9.68%). No marked evidence of clinical illness was recorded in exposed individuals. It was concluded that continuous exposure to NDV initiated antibody response in humans without causing clinical illness.
Keywords: NDV; HI; RDE; Poultry workers